Organizational psychology : an experiential approach - Kolb, David A.; Rubin, Irwin M. ;McIntyre, James M. (New Jersey : Prentice-Hall, 1979)
This book is intended for students, managers, and behavioral scientists who wish to explore the personal relevance and conceptual bases of the phenomena of organizational psychology. This book was designed with a focus on exercises, games, and role plays to make the insights of behavioral science meaningful and relevant to practicing managers and students of organizational behavior. After several years of experimentation with the classic educational methodologies lectures, seminars, research project teams, and some newer approaches such as sensitivity training -we discovered for ourselves the power of the experience-based learning model (others had made similar discoveries long before). As we began to experiment seriously with this model, within the university and in our outside consulting activities, we saw that it is possible to design an educational intervention that facilitates each stage. of the experience-based learning process. Exercises and simulations can be designed to produce experiences that create the phenomena of organizational psychology. Observation schemes and methods can be introduced to facilitate understanding of these experiences. Theories and models can be added to aid in forming generalizations. And finally, the intervention can be structured in a way that encourages the learner to experiment with what he has learned in new experiences related to his personal life. The seventeen units in this book represent our attempts to apply this approach to key concepts in organizational psychology. There is also to be a companion book, Readings in Organizational Psychology, published by Prentice-Hall, Inc. Many footnotes in this volume make reference to articles which have been reprinted there. That these articles appear in our readings book will be denoted by "Readings" at the end of the footnote entry.
Chapter 1. Basic Human Process -- Chapter 2. Organizational Socialization -- Chapter 3. Individual Motivation and Behavior -- Chapter 4. Motivation and Work -- Chapter 5. Motivation and Work -- Chapter 6. Interpersonal Communication -- Chapter 7. Interpersonal Perception -- Chapter 8. Group Dynamics -- Chapter 9. Leadership and Decision Making -- Chapter 10. Leadership: Supervision and Employee Development -- Chapter 11. Leadership: The Effective Exercise of Power and Influence -- Chapter 12. Managing Conflict Among Groups -- Chapter 14. Organization Design: Organization Structure and Communication Work -- Chapter 15. The Organization as an Open System -- Chapter 16. Planned Change and Organization Development -- Chapter 17. Personal Growth and Career Development.
Includes bibliographical references.
Keywords: PSYCHOLOGY -- INDUSTRIAL